Lecithin’s Roles in Oleogelation - Joanna Harasym; Karol Banaś (Gels, 2024)
This manuscript analyzes the research considering the exploitation of lecithin in oleogelation. The main objective of the work was to gather, analyze, and extract from the existing research data the information that enables us to identify lecithin-dependent roles. Oleogelation is still under research, while using various oleogelators and structurants provides changes on different physico-chemical levels. Multivariable formulations do not facilitate the elucidation of the specific role of any of them. Lecithin, due to its complex structure, big molecule, and amphiphilic nature, can provide different functionalities in complex matrices like oleogels. Therefore, this review identifies and categorizes the functionality of lecithin in oleogelation into four main roles: 1. oleogelation facilitator; 2. structure-forming impact; 3. texturing agent; and 4. functionality provider. Also, the origin and structure-forming characteristics of lecithin, as well as a short summary of the oleogelation process itself, are presented. Our critical analysis allowed us to identify the roles of lecithin in the oleogelation process and categorized them as follows: oleogelator, emulsifier, structural organization facilitator, structural modifier, crystal characteristics modifier, self-assembly promoter, thermal behavior changer, hydrogen-bonded networks promoter, hydrogel structure modifier, texture and structural modifier, gel-like state promoter, oil capacity enhancer, functionality provider, shelf life extender, and bioavailability and bioaccessibility enhancer. Lecithin came out as an important and multifunctional compound whose applications in oleogelation need to be thoroughly pre-considered. It is crucial to grasp all the possible roles of used compounds to be able to predict the final functionality and characteristics of formed oleogel matrices.